2016
DOI: 10.1186/s12941-016-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of plasmid-mediated NDM-1-producing Klebsiella pneumoniae ST105 among neonatal patients in Yunnan, China

Abstract: BackgroundIn the past decade, the carbapenemase-producing Enterobacteriaceae (CPE) have been reported worldwide. Emergence of carbapenemase-producing strains among Enterobacteriaceae has been a challenge for treatment of clinical infection. The present study was undertaken to investigate the characteristics of carbapenem-resistant Klebsiella pneumoniae recovered from an outbreak that affected 17 neonatal patients in neonatal intensive care unit (NICU) of Kunming City Maternal and Child health Hospital, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 30 publications
1
50
2
Order By: Relevance
“…Other plasmid replicon groups, including IncF, IncR, IncCol, L/M, and A/C, have also been described in NDM‐producing K. pneumoniae in Australia, China, Mexico, and Vietnam (Fig. ) . Furthermore, other Klebsiella spp., such as K. oxytoca , do not have a wide distribution of replicon groups, as only the IncN and IncF groups have been described in them in few countries (Table ).…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 97%
See 2 more Smart Citations
“…Other plasmid replicon groups, including IncF, IncR, IncCol, L/M, and A/C, have also been described in NDM‐producing K. pneumoniae in Australia, China, Mexico, and Vietnam (Fig. ) . Furthermore, other Klebsiella spp., such as K. oxytoca , do not have a wide distribution of replicon groups, as only the IncN and IncF groups have been described in them in few countries (Table ).…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 97%
“…These narrow‐host range (IncF) plasmids are not only responsible for disseminating KPC, but also NDM in E. coli and K. pneumoniae . Multiple plasmids have been reported, since 2012 and until recently, to carry NDM variants, particularly on IncFIB and IncFII plasmid types in K. pneumoniae and E. coli , respectively (Table and Fig.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-presence of ESBLs and NDM in the same isolate was high (78.5%, 106/135), but dual carbapenemase prevalence was fortunately low (1/135 with bla VIM-1 + bla NDM , 2/135 with bla OXA-181 + bla NDM ) [Biedenbach 2015]. A nosocomial outbreak declared in March 2014 of 19 K. pneumoniae ST10 in the neonatal intensive care unit of a Chinese hospital found that all isolates harbored bla NDM-1 on conjugative IncFI plasmids and that co-production of bla IMP-4 was common (36.8%, 7/19) but fortunately so was tigecycline, amikacin, and ciprofloxacin susceptibility [Zheng 2016]. K. pneumoniae was overwhelmingly responsible for NDM production in CRE colonized patients (370/374 patients) from Poland, a non-endemic area, during a 2012–2014 outbreak [Baraniak 2016].…”
Section: Ndmmentioning
confidence: 99%
“…NDM-1, a carbapenemase, was first detected in Sweden in a patient previously hospitalized in India [2]. Since then, NDM-1-positive K. pneumoniae strains have been sequentially reported in many other countries [3,4] - a reminder that the dissemination of NDM-1-producing K. pneumoniae could spread throughout the world. NDM-1 can hydrolyze all β-lactam antibiotics except aztreonam; furthermore, it cannot be inhibited by β-lactam inhibitors [5].…”
Section: Introductionmentioning
confidence: 99%